Regenerated-native polyurethane foaming composite material, preparation method and application thereof, and sole

By adding chain extenders and other materials to the regenerated polyurethane and using supercritical foaming method, a regeneration-native polyurethane foaming composite material with improved mechanical properties and reduced density was prepared, which solved the problems of large density and poor shrinkage resistance of regenerated polyurethane foaming products, and improved its application performance in sole materials.

CN119798959APending Publication Date: 2025-04-11CHINA LEATHER & FOOTWEAR IND RES INST JINJIANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510050713.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The high density of recycled polyurethane foamed products, poor shrinkage resistance and poor mechanical properties, limiting their application in sole materials.

Method used

Regenerated polyurethane foamed composite materials were prepared by crushing the recovered polyurethane foamed sole and mixing it with a chain extender for melt blending. The supercritical foaming method was used to prepare regenerated-native polyurethane foaming composite materials.

Benefits of technology

It improves the tensile properties, impact strength and elastic modulus of recycled polyurethane, reduces the density and compression permanent deformation of foamed composite materials, and enhances its application performance in sole materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239875600000131
    Figure BDA0005239875600000131
Patent Text Reader

Abstract

The invention provides a regenerated-native polyurethane foaming composite material, a preparation method and application thereof, and a shoe sole, and belongs to the technical field of foaming materials. According to the invention, the regenerated polyurethane is firstly subjected to chain extension modification, so that the problem that the tensile property, the impact strength, the elastic modulus and other mechanical properties of the regenerated polyurethane and the melt strength are greatly reduced is solved; meanwhile, the density, the resilience and the compression permanent deformation recovery rate of the foaming composite material are reduced by utilizing the low density, the good resilience and the elastic recovery of the thermoplastic polyamide elastomer; and the fluidity, tensile strength and elongation at break of the foamed composite material are improved by utilizing the high strength of the styrene-butadiene-styrene block copolymer and the good processability and toughening effect of the polyolefin elastomer. Therefore, the regenerated-native polyurethane foaming composite material provided by the invention has the characteristics of light weight, high resilience, high tensile strength, high elongation at break and low compression set.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a recycled-virgin polyurethane foaming composite material, a preparation method and application thereof, and a shoe sole. Background Art

[0002] Supercritical foaming technology is the hottest high-tech in the field of footwear materials in recent years. The foaming gas used is nitrogen separated from the air, and carbon dioxide extracted and reused from the tail gas of chemical or brewing. It does not produce toxic and harmful substances such as azodicarbonamide, ammonia, acetophenone, 2-phenylisopropanol, etc. used in chemical foaming in the traditional footwear industry, and it provides good protection for both producers and consumers. It does not use cross-linking agents, and the foamed thermoplastic elastomer can be melted and recycled, which is a green and environmentally friendly foaming method. Supercritical foaming footwear materials have more delicate and uniform pores, which can achieve high performance requirements of lighter weight, high resilience, and low compression permanent deformation.

[0003] Thermoplastic polyurethane (TPU) is composed of rigid segments and soft segments. The rigid segments bring good mechanical strength, while the soft segments give low-temperature flexibility, high gas solubility and gas diffusivity. TPU is relatively easy to process and has high production efficiency in supercritical foaming. Compared with nylon elastomers, it has great advantages in raw material cost. It is the most popular and widely used foaming material in supercritical physical foaming shoe materials.

[0004] However, a large amount of unexpanded materials and scraps, as well as expanded scraps and unqualified semi-finished products, are generated during the shoe production process. The waste has a complex structure and is difficult to recycle, with low recycling rates. Traditional recycling methods include landfill, incineration, and chemical degradation, but waste cannot be biodegraded in the soil; reburning will produce a large amount of particulate matter, greenhouse gases, SO 2 and NO x Photochemical toxic gases such as chlorinated ...

[0005] During the regeneration process, mechanical effects such as shearing and stretching and aging effects such as light, heat and oxygen cause the polyurethane molecular chains to break and the overall active groups to decrease, resulting in a significant decrease in the mechanical properties such as tensile properties, impact strength and elastic modulus and melt strength of the recycled polyurethane material. The decrease in melt strength brings about defects such as higher density and poor shrinkage resistance. These defects limit the application of recycled polyurethane foam materials in sole materials. Summary of the invention

[0006] The purpose of the present invention is to provide a recycled-virgin polyurethane foam composite material and a preparation method and application thereof, and a sole, which can solve the problems of large density, poor anti-shrinkage performance and poor mechanical properties of current recycled polyurethane foam products.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a recycled-virgin polyurethane foam composite material, comprising the following raw materials in parts by weight:

[0009] 50-90 parts of virgin polyurethane, 10-50 parts of recycled polyurethane, 3-15 parts of thermoplastic polyamide elastomer, 3-10 parts of styrene-butadiene-styrene block copolymer, 5-20 parts of polyolefin elastomer, 1-15 parts of inorganic reinforcing filler, and 0.1-5 parts of compatibilizer;

[0010] The preparation method of the regenerated polyurethane comprises the following steps:

[0011] After the recycled polyurethane foam soles are crushed, the obtained recycled granular materials are mixed with a chain extender, and melt blended to obtain recycled polyurethane; the chain extender includes one or more of ethylene glycol, 1,4-butanediol, hydroquinone dihydroxyethyl ether, and diethyltoluenediamine;

[0012] The thermoplastic polyamide elastomer is thermoplastic polyamide elastomer 12, and the melting point is 140-180°C.

[0013] Preferably, the mass ratio of the recycled granular material to the chain extender is 100:0.5-2; the temperature of the melt blending is 125-160° C., and the time is 3-15 min.

[0014] Preferably, the inorganic reinforcing filler includes one or more of fumed silica, furnace black, calcium carbonate and talc.

[0015] Preferably, the compatibilizer includes one or more of maleic anhydride grafted polymer, ethylene-n-butyl acrylate-methyl glycidyl ester copolymer, ethylene-butyl acrylate copolymer and ethylene-methyl acrylate copolymer.

[0016] The present invention provides a method for preparing the recycled-virgin polyurethane foam composite material described in the above technical solution, comprising the following steps:

[0017] Mixing virgin polyurethane, recycled polyurethane, thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic reinforcing filler and compatibilizer to obtain a mixed material;

[0018] The mixed material is sequentially melt-extruded and underwater granulated to obtain composite beads;

[0019] The composite beads are subjected to a foaming reaction under supercritical gas conditions to obtain a recycled-original polyurethane foam composite material.

[0020] Preferably, the mixing temperature is 40-80° C. and the mixing time is 20-30 min.

[0021] Preferably, the temperature range of the melt extrusion is 110-180°C, the time is 10-30 min, and the temperature of the underwater granulation is 190-240°C.

[0022] Preferably, the supercritical gas includes one or both of supercritical carbon dioxide and supercritical nitrogen; the conditions of the foaming reaction include: a foaming temperature of 90 to 140° C., a foaming pressure of 7 to 18 MPa, and a pressure holding time of 0.5 to 3 h.

[0023] The present invention provides application of the regenerated-original polyurethane foam composite material described in the above technical solution in the field of shoe materials.

[0024] The invention provides a shoe sole, which is made by steam molding the recycled-original polyurethane foam composite material described in the above technical solution.

[0025] The present invention provides a regenerated-original polyurethane foam composite material, and the raw materials for preparation include regenerated polyurethane, original polyurethane, thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic reinforcing filler and compatibilizer. The present invention first performs chain extension modification on the recycled polyurethane, improves the problem that the tensile properties, impact strength and elastic modulus and other mechanical properties of the regenerated polyurethane and the melt strength are greatly reduced, and at the same time, the low density, good rebound and elastic recovery of the thermoplastic polyamide elastomer 12 are used to reduce the density, rebound and compression permanent deformation recovery rate of the foam composite material, and the high strength of the styrene-butadiene-styrene block copolymer and the good processing performance and toughening effect of the polyolefin elastomer are used to improve the fluidity, tensile strength and elongation at break of the foam composite material. Therefore, the regenerated-original polyurethane foam composite material provided by the present invention has the characteristics of light weight, high rebound, high tensile strength, high elongation at break and low compression permanent deformation, and can solve the problems of large density, poor anti-shrinkage performance and poor mechanical properties of the current regenerated polyurethane foam products.

[0026] The invention adopts a supercritical foaming method to prepare a regenerated-original polyurethane foam composite material, and its performance can be further improved through reasonable formula design and improvement of the regeneration method. DETAILED DESCRIPTION

[0027] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.

[0028] The present invention provides a recycled-virgin polyurethane foam composite material, comprising the following raw materials in parts by weight:

[0029] 50-90 parts of virgin polyurethane, 10-50 parts of recycled polyurethane, 3-15 parts of thermoplastic polyamide elastomer, 3-10 parts of styrene-butadiene-styrene block copolymer, 5-20 parts of polyolefin elastomer, 1-15 parts of inorganic reinforcing filler, and 0.1-5 parts of compatibilizer;

[0030] The preparation method of the regenerated polyurethane comprises the following steps:

[0031] After the recycled polyurethane foam soles are crushed, the obtained recycled granular materials are mixed with a chain extender, and melt blended to obtain recycled polyurethane; the chain extender includes one or more of ethylene glycol, 1,4-butanediol, hydroquinone dihydroxyethyl ether, and diethyltoluenediamine;

[0032] The thermoplastic polyamide elastomer is thermoplastic polyamide elastomer 12, and the melting point is 140-180°C.

[0033] The raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 50 to 90 parts of virgin polyurethane, preferably 55 to 80 parts, and more preferably 60 to 70 parts by weight. The virgin polyurethane described in the present invention is commercially available polyurethane.

[0034] Based on the mass fraction of the virgin polyurethane, the raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 10 to 50 parts of recycled polyurethane, preferably 20 to 45 parts, more preferably 25 to 40 parts, and further preferably 30 to 35 parts.

[0035] In the present invention, the preparation method of the regenerated polyurethane comprises the following steps:

[0036] After the recycled polyurethane foamed sole is crushed, the obtained recycled granular material is mixed with a chain extender and melt-blended to obtain recycled polyurethane.

[0037] The present invention has no special limitation on the source of the recycled polyurethane foam sole, and the polyurethane foam sole can be recycled according to sources well known in the art.

[0038] In the present invention, the chain extender includes one or more of ethylene glycol, 1,4-butanediol, hydroquinone dihydroxyethyl ether, and diethyltoluenediamine, and more preferably ethylene glycol and / or 1,4-butanediol; when the chain extender is two or more of the above, the present invention has no special limitation on the ratio of different types of chain extenders, and any ratio is acceptable; in the embodiment of the present invention, the specific ratio is ethylene glycol and 1,4-butanediol at a mass ratio of 4:1.

[0039] In the present invention, the recycled granular material is preferably melt-defoamed in an open mill and then melt-blended with a chain extender, and then crushed into regenerated polyurethane fragments by a crusher, and dried at 40-60° C. for 12 hours to obtain regenerated polyurethane. The present invention has no special limitation on the melt defoaming, and can be carried out according to a process well known in the art.

[0040] In the present invention, the mass ratio of the recycled granular material to the chain extender is preferably 100:0.5-2, more preferably 100:0.5-1; the temperature of the melt blending is preferably 125-160°C, more preferably 140-150°C, and the time is preferably 3-15 min, more preferably 5-10 min.

[0041] In the present invention, the chain extender reacts with the functional groups on the recycled polyurethane molecular chain to extend the molecular chain, increase the molecular weight, improve the melt strength of the recycled polyurethane, increase the intermolecular force of the polyurethane, and improve its strength, toughness, elongation at break and other mechanical properties.

[0042] Based on the mass fraction of the virgin polyurethane, the raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 3 to 15 parts of thermoplastic polyamide elastomer, preferably 5 to 12 parts; the thermoplastic polyamide elastomer is thermoplastic polyamide elastomer 12, and the melting point of the thermoplastic polyamide elastomer 12 is 140 to 180° C., preferably 152 to 160° C. The thermoplastic polyamide elastomer 12 selected in the present invention has a processing temperature close to that of TPU, which is convenient for processing.

[0043] The present invention has no particular limitation on the source and specific brand of the thermoplastic polyamide elastomer 12, and any commercially available product known in the art may be used.

[0044] In the present invention, thermoplastic polyamide elastomer 12 (TPAE12) is formed by condensation of a high-melting-point crystalline polyamide hard segment and a non-crystalline polyether or polyester soft segment. The hard segment gives it excellent toughness, chemical resistance (acid, alkali and organic solvent), wear resistance and thermal stability; the soft segment gives it properties such as low density, low-temperature elasticity and high elastic recovery, thereby improving the corresponding performance of the polyurethane foam material.

[0045] Based on the mass fraction of the original polyurethane, the raw materials for preparing the recycled-original polyurethane foam composite material provided by the present invention include 3 to 10 parts of styrene-butadiene-styrene block copolymer, preferably 5 to 10 parts.

[0046] In the present invention, styrene-butadiene-styrene block copolymer (SBS) is a triblock copolymer with styrene and butadiene as monomers, which has the characteristics of high elasticity, excellent tensile strength, large surface friction coefficient, good low temperature performance and other rubber properties, and also has the characteristics of easy processing of plastics, and is mainly used as rubber sole products, toughening modifiers, etc. When used as a toughening modifier, a small amount of SBS blending can significantly improve the tensile properties and impact properties of the product.

[0047] Based on the mass fraction of the virgin polyurethane, the raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 5 to 20 parts of polyolefin elastomer, preferably 10 to 15 parts.

[0048] In the present invention, the polyolefin elastomer (POE) is a thermoplastic elastomer polymerized by ethylene and octene under the action of a metallocene catalyst. The soft chains of octene and the crystallized ethylene chains serve as physical crosslinking points, which enable it to play a connecting role between the various parts. When subjected to impact or tension, it can disperse and buffer energy, reduce the chance of silver streaks developing into cracks due to stress, thereby improving the impact strength, tensile strength and elongation at break of the system, and serve as a toughening matrix in the foamed composite material.

[0049] Based on the mass fraction of the virgin polyurethane, the raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 1 to 15 parts of inorganic reinforcing filler, preferably 5 to 12 parts, and more preferably 7 to 10 parts. In the present invention, the inorganic reinforcing filler preferably includes one or more of fumed silica, furnace carbon black, calcium carbonate and talcum powder, more preferably fumed silica and talcum powder; when the inorganic reinforcing filler is two or more of the above, the present invention has no special restrictions on the ratio of different types of inorganic reinforcing fillers, and any ratio is acceptable. The present invention uses inorganic reinforcing fillers to reinforce the composite foam material, improve its physical properties such as tensile strength, and can be used as a nucleating agent in the foaming process to improve the pore structure of the composite foam material.

[0050] Based on the mass fraction of the virgin polyurethane, the raw materials for preparing the recycled-virgin polyurethane foam composite material provided by the present invention include 0.1 to 5 parts of a compatibilizer, preferably 0.5 to 4 parts, and more preferably 1 to 2 parts. In the present invention, the compatibilizer preferably includes one or more of a maleic anhydride grafted polymer, an ethylene-butyl acrylate-methyl glycidyl ester copolymer, an ethylene-butyl acrylate copolymer, and an ethylene-methyl acrylate copolymer, and the maleic anhydride grafted polymer is preferably a maleic anhydride grafted styrene-butadiene-styrene block copolymer. When the compatibilizer is two or more of the above, the present invention has no special restrictions on the ratio of different types of compatibilizers, and any ratio is acceptable. In the present invention, the compatibilizer can reduce the interfacial tension between thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer, polyolefin elastomer and recycled-virgin polyurethane, improve the compatibility of different components in the composite foaming material, and improve the tensile strength and other mechanical properties of the composite foaming material.

[0051] The present invention provides a method for preparing the recycled-virgin polyurethane foam composite material described in the above technical solution, comprising the following steps:

[0052] Mixing virgin polyurethane, recycled polyurethane, thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic reinforcing filler and compatibilizer to obtain a mixed material;

[0053] The mixed material is sequentially melt-extruded and underwater granulated to obtain composite beads;

[0054] The composite beads are subjected to a foaming reaction under supercritical gas conditions to obtain a recycled-original polyurethane foam composite material.

[0055] In the present invention, the mixing temperature is preferably 40 to 80° C., preferably 60 to 80° C., and the mixing time is preferably 20 to 30 min, more preferably 22 to 25 min; and the mixing is preferably carried out in a high-speed mixer.

[0056] In the present invention, the melt extrusion temperature range is preferably 110-180°C, preferably 120-170°C; the time is preferably 10-30 min, more preferably 15-25 min; the underwater granulation temperature is preferably 190-240°C, more preferably 195-225°C.

[0057] In the present invention, the mixed material is preferably melted in a twin-screw extruder, mixed and extruded, and then pelletized in an underwater pelletizing system, and the obtained composite beads are subjected to a foaming reaction in a supercritical reactor.

[0058] In the present invention, the supercritical gas preferably includes one or both of supercritical carbon dioxide and supercritical nitrogen; the conditions of the foaming reaction preferably include: the foaming temperature is 90-140°C, preferably 115-125°C, the foaming pressure is 7-18MPa, preferably 10-12MPa, and the pressure holding time is 0.5-3h, more preferably 1-1.5h.

[0059] The present invention provides application of the regenerated-original polyurethane foam composite material described in the above technical solution in the field of shoe materials.

[0060] The present invention provides a sole, which is made by steam molding the recycled-virgin polyurethane foam composite material described in the above technical solution. The temperature of the steam molding is preferably 90-110° C., more preferably 105° C. The present invention has no special restrictions on the specific manufacturing process of the sole, and it can be carried out in a manner well known in the art.

[0061] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0062] In the following examples, the raw materials used and their sources are:

[0063] Virgin polyurethane: polyurethane S85A, BASF Polyurethane Specialties (China) Co., Ltd.;

[0064] Thermoplastic polyamide elastomer 12 (TPAE12), Dongguan Baitong New Materials Co., Ltd.;

[0065] Styrene-butadiene-styrene block copolymer CH301, Ningbo Changhong Polymer Technology Co., Ltd.;

[0066] Polyolefin elastomer, POE6102, ExxonMobil Corporation, USA;

[0067] Reinforcement filler: fumed silica, 185, Fujian Shaxian Jinsha Silica Manufacturing Co., Ltd., furnace carbon black, N330, Cabot Corporation, USA;

[0068] Compatibilizer: maleic anhydride grafted styrene-butadiene-styrene block copolymer (MAH-SBS), CH909, Guangdong Chuanheng New Materials Technology Co., Ltd.;

[0069] Chain extender: ethylene glycol, Nanjing Rongji Chemical Co., Ltd.; 1,4-butanediol, Guangdong Yuemei Chemical Co., Ltd.

[0070] Example 1

[0071] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0072] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, 1215 parts of thermoplastic polyamide elastomer, 10 parts of styrene-butadiene-styrene block copolymer, 10 parts of polyolefin elastomer, 7 parts of reinforcing filler, and 1 part of compatibilizer.

[0073] The preparation method of recycled polyurethane is as follows: recycled polyurethane foamed soles are crushed into fragments in a crusher, 1000g of the obtained recycled granular materials and 5g of chain extender are melt-blended and defoamed at 140°C for 10 minutes in an open mill, crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60°C for 12 hours to obtain recycled polyurethane; the chain extender is ethylene glycol and 1,4-butanediol, and the mass ratio of ethylene glycol to 1,4-butanediol is 4:1.

[0074] The melting point of the thermoplastic polyamide elastomer 12 is 152° C.; the reinforcing filler is fumed silica; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0075] The preparation method is as follows:

[0076] 1) mixing recycled polyurethane, virgin polyurethane, thermoplastic polyamide elastomer 12, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic filler and compatibilizer in a high-speed mixer at 80° C. for 25 min to obtain a mixed material;

[0077] 2) The mixed material is melted in a twin-screw extruder and then mixed and extruded to obtain a mixed material. The temperatures of the 8 zones of the extruder are 120° C., 130° C., 135° C., 140° C., 145° C., 155° C., 160° C., and 165° C. in sequence. The total time is 30 minutes, and each time period is the same.

[0078] 3) pelletizing the mixed material in an underwater pelletizing system at 195° C. to obtain composite beads;

[0079] 4) reacting the composite beads with supercritical carbon dioxide at 115° C. and 12 MPa for 1.5 h in a supercritical reactor to obtain a recycled-virgin polyurethane foam composite material.

[0080] Example 2

[0081] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0082] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, 123 parts of thermoplastic polyamide elastomer, 3 parts of styrene-butadiene-styrene block copolymer, 5 parts of polyolefin elastomer, 7 parts of reinforcing filler and 1 part of compatibilizer.

[0083] The preparation method of recycled polyurethane is as follows: the recycled polyurethane foamed sole is crushed into pieces in a crusher, 1000g of the obtained recycled granular material and 5g of chain extender are melt-blended and defoamed at 140°C for 10 minutes in an open mill, and finally crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60°C for 12 hours to obtain recycled polyurethane; the chain extender is ethylene glycol.

[0084] The melting point of the thermoplastic polyamide elastomer 12 is 152° C.; the reinforcing filler is fumed silica; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0085] The preparation method is the same as Example 1.

[0086] Example 3

[0087] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0088] 30 parts of recycled polyurethane, 70 parts of virgin polyurethane, 1215 parts of thermoplastic polyamide elastomer, 10 parts of styrene-butadiene-styrene block copolymer, 20 parts of polyolefin elastomer, 7 parts of reinforcing filler and 1 part of compatibilizer.

[0089] The preparation method of recycled polyurethane is as follows: recycled polyurethane foamed soles are crushed into pieces in a crusher, 1000g of the obtained recycled granular materials are melt-blended with 5g of a chain extender at 140°C for defoaming for 10 minutes in an open mill, and finally crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60°C for 12 hours to obtain recycled polyurethane; the chain extender is ethylene glycol and 1,4-butanediol, and the mass ratio is 4:1.

[0090] The melting point of the thermoplastic polyamide elastomer 12 is 152° C.; the reinforcing filler is furnace carbon black; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0091] The preparation method is the same as Example 1.

[0092] Example 4

[0093] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0094] 30 parts of recycled polyurethane, 70 parts of virgin polyurethane, 123 parts of thermoplastic polyamide elastomer, 3 parts of styrene-butadiene-styrene block copolymer, 5 parts of polyolefin elastomer, 7 parts of reinforcing filler and 1 part of compatibilizer.

[0095] The preparation method of recycled polyurethane is as follows: recycled polyurethane foamed soles are crushed into pieces in a crusher, 1000g of the obtained recycled granular materials are melt-blended with 5g of a chain extender at 140°C for defoaming for 10 minutes in an open mill, and finally crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60°C for 12 hours to obtain recycled polyurethane; the chain extender is ethylene glycol and 1,4-butanediol, and the mass ratio is 4:1.

[0096] The melting point of the thermoplastic polyamide elastomer 12 is 152° C.; the reinforcing filler is fumed silica; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0097] The preparation method is the same as Example 1.

[0098] Comparative Example 1

[0099] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0100] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, 10 parts of styrene-butadiene-styrene block copolymer, 10 parts of polyolefin elastomer, 7 parts of reinforcing filler, and 1 part of compatibilizer.

[0101] The preparation of recycled polyurethane is the same as in Example 1.

[0102] The reinforcing filler is fumed silica; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0103] The preparation method is as follows:

[0104] 1) mixing recycled polyurethane, virgin polyurethane, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic filler and compatibilizer in a high-speed mixer at 80° C. for 25 minutes to obtain a mixed material;

[0105] 2) The mixed material is melted in a twin-screw extruder and then mixed and extruded to obtain a mixed material. The temperatures of the 8 zones of the extruder are 120° C., 130° C., 135° C., 140° C., 145° C., 155° C., 160° C., and 165° C. in sequence. The total time is 30 minutes, and each time period is the same.

[0106] 3) pelletizing the mixed material in an underwater pelletizing system at 195° C. to obtain composite beads;

[0107] 4) reacting the composite beads with supercritical carbon dioxide at 115° C. and 12 MPa for 1.5 h in a supercritical reactor to obtain a recycled-virgin polyurethane foam composite material.

[0108] Comparative Example 2

[0109] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, 10 parts of polyolefin elastomer, 7 parts of reinforcing filler, and 1 part of compatibilizer.

[0110] The preparation of recycled polyurethane is the same as in Example 1.

[0111] The reinforcing filler is fumed silica; and the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer.

[0112] The preparation method is as follows:

[0113] 1) mixing recycled polyurethane, virgin polyurethane, polyolefin elastomer, reinforcing filler and compatibilizer in a high-speed mixer at 80° C. for 25 min to obtain a mixed material;

[0114] 2) The mixed material is melted in a twin-screw extruder and then mixed and extruded to obtain a mixed material. The temperatures of the 8 zones of the extruder are 120° C., 130° C., 135° C., 140° C., 145° C., 155° C., 160° C., and 165° C. in sequence. The total time is 30 minutes, and each time period is the same.

[0115] 3) pelletizing the mixed material in an underwater pelletizing system at 195° C. to obtain composite beads;

[0116] 4) reacting the composite beads with supercritical carbon dioxide at 115° C. and 12 MPa for 1.5 h in a supercritical reactor to obtain a recycled-virgin polyurethane foam composite material.

[0117] Comparative Example 3

[0118] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0119] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, 10 parts of styrene-butadiene-styrene block copolymer, 10 parts of polyolefin elastomer, 7 parts of reinforcing filler, and 1 part of compatibilizer.

[0120] The preparation method of recycled polyurethane is as follows: the recycled polyurethane foam sole is crushed into pieces in a crusher, melt-blended and defoamed at 140° C. in an open mill for 10 minutes, and finally crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60° C. for 12 hours to obtain recycled polyurethane.

[0121] The reinforcing filler is fumed silica; the compatibilizer is maleic anhydride grafted styrene-butadiene-styrene block copolymer;

[0122] The preparation method is as follows:

[0123] 1) mixing recycled polyurethane, virgin polyurethane, styrene-butadiene-styrene block copolymer, polyolefin elastomer, reinforcing filler and compatibilizer in a high-speed mixer at 80° C. for 25 minutes to obtain a mixed material;

[0124] 2) The mixed material is melted in a twin-screw extruder and then mixed and extruded to obtain a mixed material. The temperatures of the 8 zones of the extruder are 120° C., 130° C., 135° C., 140° C., 145° C., 155° C., 160° C., and 165° C. in sequence. The total time is 30 minutes, and each time period is the same.

[0125] 3) pelletizing the mixed material in an underwater pelletizing system at 195° C. to obtain composite beads;

[0126] 4) reacting the composite beads with supercritical carbon dioxide at 115° C. and 12 MPa for 1.5 h in a supercritical reactor to obtain a recycled-virgin polyurethane foam composite material.

[0127] Comparative Example 4

[0128] A recycled-virgin polyurethane foam composite material is prepared from the following raw materials in parts by weight:

[0129] 40 parts of recycled polyurethane, 60 parts of virgin polyurethane, and 7 parts of reinforcing filler.

[0130] The preparation method of recycled polyurethane is as follows: the recycled polyurethane foam sole is crushed into pieces in a crusher, melt-blended and defoamed in an open mill at 140° C. for 10 minutes, and finally crushed into recycled polyurethane fragments by a crusher, and the recycled polyurethane fragments are dried at 60° C. for 12 hours.

[0131] Wherein, the reinforcing filler is fumed silica.

[0132] The preparation method is as follows:

[0133] 1) Mixing recycled polyurethane, virgin polyurethane and reinforcing filler in a high-speed mixer at 80° C. for 25 minutes to obtain a mixed material;

[0134] 2) The mixed material is melted in a twin-screw extruder and then mixed and extruded to obtain a mixed material. The temperatures of the 8 zones of the extruder are 120° C., 130° C., 135° C., 140° C., 145° C., 155° C., 160° C., and 165° C. in sequence. The total time is 30 minutes, and each time period is the same.

[0135] 3) pelletizing the mixed material in an underwater pelletizing system at 195° C. to obtain composite beads;

[0136] 4) reacting the composite beads with supercritical carbon dioxide at 115° C. and 12 MPa for 1.5 h in a supercritical reactor to obtain a recycled-virgin polyurethane foam composite material.

[0137] Performance Testing

[0138] The density of the recycled-virgin polyurethane foam composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was tested;

[0139] The recycled-virgin polyurethane foam composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively steam-formed at 105° C. to prepare foam products, and the hardness, tensile strength, elongation at break, rebound and compression set properties were tested.

[0140] Among them, the density is tested according to the national standard GB / T 533-2008; the hardness is tested according to the national standard GB / T3903.4-2017; the tensile strength and elongation at break are tested according to the national standard GB / T528-2009; the resilience is tested according to the national standard GB / T 1681-2009; and the compression set is tested according to the industry standard HG / T 2876-2009. The results are shown in Table 1.

[0141] Table 1 Comparison of technical parameters of recycled-virgin polyurethane foam composite materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4

[0142]

[0143] As can be seen from Table 1, the performance test results of Comparative Examples 1 to 4 show that the higher the amount of thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer and polyolefin elastomer used, the better the various properties of the composite material; from the performance test results of Comparative Example 1 and Comparative Example 1, it can be seen that the addition of thermoplastic polyamide elastomer greatly reduces the density of the composite foam material (indicating a large foaming ratio), slightly reduces the hardness and compression permanent deformation, and significantly improves the rebound, tensile strength and elongation at break; from Comparative Example 2, it can be seen that the addition of styrene-butadiene-styrene block copolymer and thermoplastic polyamide elastomer slightly reduces the density, hardness and compression permanent deformation of the composite foam material, and slightly improves the rebound and tensile strength; the various properties of the composite foam material in Comparative Example 3 that is not subjected to chain extension modification are further deteriorated; the density, hardness, compression permanent deformation, rebound and tensile strength and other properties of the composite foam material in Comparative Example 4 that is not added with polyolefin elastomer, styrene-butadiene-styrene block copolymer and thermoplastic polyamide elastomer are further deteriorated.

[0144] It can be seen from the performance test results of Examples 1 to 4 and Comparative Examples 1 to 4 that the recycled-virgin polyurethane foam composite material prepared by the present invention improves the various properties of the recycled polyurethane foam material, and has the advantages of low density, moderate hardness, high tensile strength, high elongation at break, good resilience, and low compression permanent deformation.

[0145] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A recycled-virgin polyurethane foam composite material, characterized in that: The preparation comprises the following raw materials in parts by weight: 50-90 parts of virgin polyurethane, 10-50 parts of recycled polyurethane, 3-15 parts of thermoplastic polyamide elastomer, 3-10 parts of styrene-butadiene-styrene block copolymer, 5-20 parts of polyolefin elastomer, 1-15 parts of inorganic reinforcing filler, and 0.1-5 parts of compatibilizer; The preparation method of the regenerated polyurethane comprises the following steps: After the recycled polyurethane foam soles are crushed, the obtained recycled granular materials are mixed with a chain extender, and melt blended to obtain recycled polyurethane; the chain extender includes one or more of ethylene glycol, 1,4-butanediol, hydroquinone dihydroxyethyl ether, and diethyltoluenediamine; The thermoplastic polyamide elastomer is thermoplastic polyamide elastomer 12, and the melting point is 140-180°C.

2. The recycled-virgin polyurethane foam composite material according to claim 1, characterized in that: The mass ratio of the recycled granular material to the chain extender is 100:0.5-2; the temperature of the melt blending is 125-160° C., and the time is 3-15 minutes.

3. The recycled-virgin polyurethane foam composite material according to claim 1, characterized in that: The inorganic reinforcing filler includes one or more of fumed silica, furnace carbon black, calcium carbonate and talc.

4. The recycled-virgin polyurethane foam composite material according to claim 1, characterized in that: The compatibilizer includes one or more of maleic anhydride grafted polymer, ethylene-n-butyl acrylate-methyl glycidyl ester copolymer, ethylene-butyl acrylate copolymer and ethylene-methyl acrylate copolymer.

5. The method for preparing the recycled-virgin polyurethane foam composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing virgin polyurethane, recycled polyurethane, thermoplastic polyamide elastomer, styrene-butadiene-styrene block copolymer, polyolefin elastomer, inorganic reinforcing filler and compatibilizer to obtain a mixed material; The mixed material is sequentially melt-extruded and underwater granulated to obtain composite beads; The composite beads are subjected to a foaming reaction under supercritical gas conditions to obtain a recycled-original polyurethane foam composite material.

6. The preparation method according to claim 5, characterized in that: The mixing temperature is 40-80° C. and the mixing time is 20-30 minutes.

7. The preparation method according to claim 5, characterized in that: The temperature range of the melt extrusion is 110-180°C, the time is 10-30 minutes, and the temperature of the underwater granulation is 190-240°C.

8. The preparation method according to claim 5, characterized in that: The supercritical gas includes one or both of supercritical carbon dioxide and supercritical nitrogen; the conditions of the foaming reaction include: a foaming temperature of 90 to 140° C., a foaming pressure of 7 to 18 MPa, and a pressure holding time of 0.5 to 3 hours.

9. Use of the regenerated-virgin polyurethane foam composite material according to any one of claims 1 to 4 or the regenerated-virgin polyurethane foam composite material prepared by the preparation method according to any one of claims 5 to 8 in the field of shoe materials.

10. A shoe sole, characterized in that: The regenerated-original polyurethane foam composite material is prepared by steam molding using the regenerated-original polyurethane foam composite material as described in any one of claims 1 to 4 or the regenerated-original polyurethane foam composite material prepared by the preparation method as described in any one of claims 5 to 8.